2018
DOI: 10.1016/j.clnu.2017.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of resting metabolic rate measurements in young adults: Impact of methods for data analysis

Abstract: The 5 min SSt approach should be the method of choice for analyzing IC measures with metabolic carts. However, achieving SS should not be an inclusion criterion in an IC study with young healthy adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 25 publications
7
51
2
Order By: Relevance
“…In the present study, all RMR measurements were included in the analysis because the conclusion of the findings remains unchanged when we stratified the data by the participants with and without a steady state. This is in line with a previous study in healthy adults which suggested that participants who do not achieve steady state should not be excluded from data analysis (47) . There is no universal definition for steady state as it varies by measurement time, the CV and combination of gas-exchange variables (VO 2 and VCO 2 ) (13) .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, all RMR measurements were included in the analysis because the conclusion of the findings remains unchanged when we stratified the data by the participants with and without a steady state. This is in line with a previous study in healthy adults which suggested that participants who do not achieve steady state should not be excluded from data analysis (47) . There is no universal definition for steady state as it varies by measurement time, the CV and combination of gas-exchange variables (VO 2 and VCO 2 ) (13) .…”
Section: Discussionsupporting
confidence: 92%
“…However, as STS is not always achieved, other methods for data analysis have been proposed, such as predefined time interval selection [5]. Sanchez-Delgado et al [6] recently showed that REE is consistently lower when following STS approach than when following time interval methods in healthy young adults. This suggests that achieving STS could provide a more valid REE measurement, given that REE is considered the lowest energy expenditure in an awake person [5].…”
Section: Methodology Of Indirect Calorimetry: What Is New?mentioning
confidence: 99%
“…However, further studies are needed to assess the best method for analyzing indirect calorimetry measurements if STS is not achieved. According to Sanchez Delgado et al [6], the selection of the five most stable minutes should be the method of choice for analyzing indirect calorimetry measures in healthy young adults. Indeed, although no significant differences were found between different durations of STS (3, 4, 5 and 10 min), 5 min STS presented the lowest REE [6].…”
Section: Methodology Of Indirect Calorimetry: What Is New?mentioning
confidence: 99%
“…The most stable 5-min period that met steady-state criteria (i.e., coefficient of variation <10% in VO 2 , CO 2 , and minute ventilation, and coefficient of variation <10% in respiratory exchange ratio (RER)) was considered for further analysis [4,5,27,28]. Participants with an RER lower than 0.7 and/or higher than 1.0 were excluded from the final analysis.…”
Section: Basal Metabolic Rate and Basal Nutrients Oxidationmentioning
confidence: 99%